Adrian Willaert : a guide to research - Kidger, David (Routledge music bibliographies., 2005)
This key text will be the first full-length research tool on Adrian Willaert, the Renaissance composer of motets and madrigals who came to prominence in the first part of the sixteenth century, and should prove invaluable to researchers and students of Renaissance music. It includes annotated entries on all published literature and a biography section with information on all well-known primary source material. Willaert was a key teacher and administrator in Renaissance Venice who helped establish Venice, and especially St. Marks, as a key centre for musical composition and performance.